Analysis of the Learning Motivation of Biology Education Students in the Implementation of Field Trip Activities for Plant Taxonomy Courses - Juwita, Fefy Dwi; Kencanawati, Indah; Qadariah, Nosi (KULIDAWA, 2024)
This study aims to evaluate the effect of field trip activities on students' learning motivation in the plant taxonomy course. It uses a survey method with a descriptive qualitative approach. The present study was conducted at IAIN Kerinci with a sample of fourth-semester students of the Biology Education Study Program in 2024 who took the plant taxonomy course. The data collection technique was a questionnaire based on learning motivation indicators, according to Uno (2008). The data were analyzed using descriptive statistics to determine the percentage of motivation for each indicator. The results showed that 41.67% of students really agree and 53% agree that field trip activities significantly increased their learning motivation. Analysis per indicator showed that motivation was driven by the desire to succeed (45.56% really agree), demands and need in learning (37.00%), future hopes and aspirations (36.67% really agree), being appreciated in learning (47.78% really agree), and a conducive learning environment   (40% really agree). However, a small number of students (5.17%) stated that this activity was less advantageous due to lack of preparation or unsupportive field conditions, so it can be concluded that the field trip method is an effective learning method to increase students' motivation and understanding, especially in practice-based courses such as plant taxonomy. However, more thorough planning is needed to optimize the benefits of this activity.